108k views
4 votes
If f(x)=2x and g(x)=x−3, then find f(x)·g(x).

Question 19 options:

2x2−6x

2x2−6

2x2−3

3x−3

User Tiasia
by
4.9k points

1 Answer

3 votes

Answer:

f(x)g(x) = 2x² - 6x

General Formulas and Concepts:

Algebra I

  • Expand by FOIL-ing (First, Outside, Inside, Last)

Explanation:

Step 1: Define

f(x) = 2x

g(x) = x - 3

Step 2: Find f(x)g(x)

  1. Substitute: f(x)g(x) = 2x(x - 3)
  2. Distribute 2x: f(x)g(x) = 2x² - 6x
User Sathish D
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.